Investment Climate in the Spa Municipalities. Case Studies - Elżbieta Inglot-Brzęk; Anna Lewandowska (Barometr Regionalny)
For the governments of individual countries and regions, actions to improve the investment climate are tools that contribute to new production and service investments, and thus to economic development. The investment climate is the result of many components. The aim of this article is to analyze the individual components of the investment climate on the example of three spa and tourist municipalities: Krasnobród, Solec Zdrój and Rymanów. The analysis provides the basis for conclusions on the desired action of local and regional authorities to improve the situation. The analysis presented in this article is the result of CATI and FGI research.